Treating Hematologic Malignancies During a Pandemic: Utilizing Telehealth and Digital Technology to Optimize Care - Binder, Adam F.; Handley, Nathan R.; Wilde, Lindsay; Palmisiano, Neil; Lopez, Ana Maria (Frontiers in Oncology, 2020)
In late January 2020, Severe Acute Respiratory Syndrome Coronavirus-2 (SARS CoV-2) was reported as an outbreak in Wuhan, China. Within 2 months it became a global pandemic. Patients with cancer are at highest risk for both contracting and suffering complications of its resultant disease, Coronavirus 19 (COVID-19). Healthcare systems across the world had to adapt quickly to mitigate this risk, while continuing to provide potentially lifesaving treatment to patients. Bringing care to the home through the use of telehealth, home based chemotherapy, and remote patient monitoring technologies can help minimize risk to the patient and healthcare workers without sacrificing quality of care delivered. These care models provide the right treatment, to the right patient, at the right time, in the right place. Whether these patient-centered models of care will continue to be embraced by key stakeholders after the pandemic remains uncertain.